A Method to Establish a Fire Information Visualization Structure for 3D/BIM-linked Fire Response System Development - Kim, Da Hee; Shin, Hyeon Ju; Cha, Hee Sung (Journal of the Architectural Institute of Korea, 2022)
During a fire, it is of utmost importance to provide reliable building information and secure a fire response system for proper and safe evacu ation of building occupants. Every building offers different and changing fire/building information. So for buildings, it is highly recommended to upgrade to an integrated 3D/BIM linked fire response system. The purpose of this upgrade to the 3D/BIM model is not solely because of the solid design, but more so for its usability and visuals to quickly extract needed building information in an emergency. In suggesting this method, the aim is to better secure a quick response from fire personnel and provide essential building information for evacuation and rescue to save lives.
Keywords: BIM; Fire response system; Information; Visualization